Genetic variability and gain for storage root yield and yield components in yam beans - Ndirigwe, J.; Rubaihayo, P.R.; Tukamuhabwe, Phineas; Agaba, R.; Tumwegamire, Silver; Mwanga, Robert O.M.; Heider, B.; Grüneberg, W.J. (African Journals Online, 2020)
There is limited information on the genetic parameters and genetic gain of yam bean (Pachyrhizus species) accessions introduced to Rwanda. No comprehensive literature exists on the inheritance of yield and yield components, on segregating populations. This study investigated variability, heritability and genetic advance in F2 yam bean genotypes. Seven F2 yam bean hybrids were evaluated at the Rubona Research Station located in Southern Province of Rwanda, during growing season 2014B. Results revealed significant (P<0.01) genetic variability in plant vigour (PV), pod weight (WOP), plant height (PHT), 100 seed weight (100SW), total biomass yield (TBY), storage root yield (SRY), dry matter content (DMC), and starch content (STA). High genetic (σ2g) and phenotypic (σ2p) variances, and genotypic coefficients of variation (GCV> 25%) were observed for WOP, PHT, 100SW, TBY, DMC and STA. Estimates of heritability (H2) were high (greater than 50%) for all traits, except for seed yield, number of roots and number of pods. The GA and genetic advance, as percentage of the mean (GAM%), were high for PV, WOP, PHT, 100SW, TBY and DMC. There were positive and significant (P<0.05) associations between PV and PHT, protein content (PRO), 100SW, TBY, SRY, and DMC. Dry matter content also had positive and significant (P<0.01) correlations with STA. These results indicate presence of high genetic variability, heritability and expected genetic gain suggesting potential for genetic improvement of plant vigour, weight of pods, plant height, 100 seed weight, total biomass yield, storage root fresh yield, dry matter content and starch content of yam beans in Rwanda.